PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN, SIKAP, DAN MOTIVASI IBU HAMIL DALAM PENERIMAAN VAKSIN COVID-19 DI PUSKESMAS CADASARI - Murni, (2022)
Background: The COVID-19 pandemic is a global crisis by the life-threatening severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Pregnant women are at high risk of contracting COVID-19. Several countries are developing vaccines to slow the impact of the pandemic. Providing education can improve knowledge, attitudes and motivation about COVID-19 vaccines. Several factors influence the acceptability of a COVID-19 vaccine are vaccine knowledge, attitudes, and motivation. Objective: To determine the impact of education on knowledge, attitudes, and motivation to vaccinate against COVID-19 in pregnant women. Methods: This study used a quasi-experimental research design the Wilcoxon test. The sampling technique Consecutive Sampling of up to 60 respondents. This research tool uses the Knowledge COVID-19 Vaccine, Attitudes towards COVID-19 Vaccine and Vaccine Motivation Questionnaire. Results: Results showed that health education had an effect on knowledge, attitudes and motivation to vaccinate before and after education (p-value 0.000). Conclusions: Health education has an impact on knowledge, attitudes, and motivation to vaccinate against COVID-19 in pregnant women. However, 15 of the 60 respondents said they would be vaccinated against COVID-19 if vaccination services were available. The researchers hope to further develop studies related to the impact of COVID-19 vaccination education on pregnant women, adding more variables.